Evaluation of Disincentive Effects of 70% Isopropyl Alcohol and 10% povidone-iodine Safety Antimicrobial Agents of Skin - Iman Fadhil Abdul-Husin (Journal of Global Pharma Technology, 2018)
Background: Many disinfectants were used clinically in both single and mixture applications, however there had been few research on disincentive electricity according to sterilization series when the use of an aggregate of disinfectants. Aim: the purpose of present study was to evaluate the antimicrobial of two disinfectants each one alone and when the usage of a combination of them on skin isolates bacteria. Methods: One hindered and eight healthy volunteers were recruited. first groups were treated with a70% isopropyl alcohol on forearm, second groups were treated with 10% povidone-iodine on forearm and third groups were treated with combination of 70% isopropyl alcohol and 10% PVP-I on forearm included disinfections on the both forearm with isopropyl alcohol first followed by 10% PVP-I. Skin cultures have been acquired the usage of cotton swabs three minutes after application of each disinfectant, and then had been inoculated on blood agar plates for bacterial lifestyle Result: There was no significant difference in the number of positive cultures between subject treated with single disinfect (first groups, 150bacterial isolates for subject treated with a 70% isopropyl alcohol; while in the second group 108bacterial isolates for subject treated with10% povidone-iodine (P < 0.01)).Third groups was more effective than disinfection with a single agent since there were only 48 bacterial isolates suggesting that there is relationship between disincentive power of mixed two disinfectants that used in present study. Conclusion: The combination of 70 % isopropyl alcohol and 10% PVP-I was more effective than disinfection with a single disinfects of them with either 70% isopropyl alcohol or 10% PVP-I disinfect.Keywords: Antimicrobial agents, 70% isopropyl alcohol, and 10% povidone –iodine.